AN EFFECTIVE BEGINNING READING METHOD IN IMPROVING STUDENTS' UNDERSTANDING OF SUBJECTS INDONESIAN LANGUAGE OF CLASS 1 AT UPT SDN 3 WAY KENANGA WEST TULANG BAWANG REGENCY - Al Qowim, Siti Bashoriyah; Azmi, Ulil (PT. Antis International Publisher, 2024)
The aim of the research is to find the right method to use in teaching beginning reading skills to grade 1 students at SDN 3 Way Kenanga. The aim of beginning reading is also explained in (Depdikbud, 1994:4), namely so that